Peran Media Sosial terhadap Pengetahuan Keagamaan Remaja Muslim - Anisatul Luthfia (Moral : Jurnal kajian Pendidikan Islam, 2025)
This study aims to analyze the role of social media and explore how it influences the views and understanding of religious knowledge among Muslim youth. Using a qualitative approach, the study provides a detailed exploration of adolescents' perceptions of religious content accessed through social media and its impact on their understanding of Islam. The findings indicate that social media plays a significant role in enhancing religious understanding among youth. The majority of participants access religious content through platforms such as Instagram and TikTok, with most feeling that this content helps them gain a deeper understanding of Islamic teachings. This positive influence includes increased motivation to engage in worship and improve daily behavior in accordance with religious principles. However, participants also noted challenges related to the quality of information, which is often inaccurate or superficial. Nonetheless, social media fosters a strong sense of community through interactions in discussion groups and collaboration in religious learning. The study concludes that while social media has great potential to enrich religious knowledge among youth, it is important for adolescents to select credible sources, and for parents and educators to provide guidance on the wise use of social media.